(untitled) - Võ, Diễm Trinh (Cần Thơ, 2018)
The first aim of the study is to investigate ICT tools EFL teachers use in listening lessons. Secondly, the study aims to explore EFL learners’ attitudes towards the EFL teachers’ use of ICT tools in listening lessons.
Keywords: Tiếng Anh,English language; Học và dạy học,Study and teaching